2018
DOI: 10.1146/annurev-marine-010816-060535
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Trapping in Estuaries

Abstract: Estuarine turbidity maxima (ETMs) are generated by a large suite of hydrodynamic and sediment dynamic processes, leading to longitudinal convergence of cross-sectionally integrated and tidally averaged transport of cohesive and noncohesive suspended particulate matter (SPM). The relative importance of these processes for SPM trapping varies substantially among estuaries depending on topography, fluvial and tidal forcing, and SPM composition. The high-frequency dynamics of ETMs are constrained by interactions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
165
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(171 citation statements)
references
References 117 publications
6
165
0
Order By: Relevance
“…One of the main characteristics of estuaries is the estuarine maximum turbidity zone (MTZ), which is the area where fluvial and marine sediments are efficiently trapped (Burchard et al, ). MTZs are often observed in coastal plain (or drowned river valley), salt wedge, and river‐dominated estuaries (Jay et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main characteristics of estuaries is the estuarine maximum turbidity zone (MTZ), which is the area where fluvial and marine sediments are efficiently trapped (Burchard et al, ). MTZs are often observed in coastal plain (or drowned river valley), salt wedge, and river‐dominated estuaries (Jay et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…MTZs are often observed in coastal plain (or drowned river valley), salt wedge, and river‐dominated estuaries (Jay et al, ). Previous studies on MTZ dynamics have shown that more than 65 estuaries in the world are known to have MTZs (e.g., Burchard et al, ; Jay et al, ; Uncles et al, ). An MTZ is a region of convergent SPM flux, where the SPM concentration is generally high (Allen et al, ; de Jonge et al, ; Postma, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sediment flow can be positive from the shelf to the estuary, especially in the dry season (e.g., [46][47][48][49][50][51]). In the Red River, for example, some of the sediments deposited in the subaqueous delta during the rainy season return in the dry season by tidal pumping to the estuary and deltaic wetlands, where deposition is three times greater than in the rainy season [52].…”
Section: Sediment Balances and Morphodynamic Evolutionmentioning
confidence: 99%
“…Sediments are then brought back from the sea to the estuary near the bottom, even in the absence of density circulation, and settle and consolidate under the control of spring-neap tide cycles. This process, described in the 1970s [46], is still under study (see [51,142]). This key mechanism of delta geomorphodynamics is very sensitive to changes in flows, and river water regulation induced by dams is enough to move the estuarine turbidity zone and cause the silting up of navigation channels and river ports, as on the Red River [157].…”
Section: Cohesive Sedimentsmentioning
confidence: 99%